Optimalisasi Proses Pendidikan Melalui Bantuan Pembelajaran Di Desa Tamberu Alet, Batumarmar, Pamekasan - Bashori, Abdul Hamid; Rohman, Moh.; Ali, Hairul; Salam, Badrus (STAI Publisistik Thawalib Jakarta, 2022)
Service is a student learning process through various activities directly in the community, and students strive to be part of the community and are actively and creatively involved in the dynamics that occur in the community. The purpose of this service is to optimize the learning process in the community. The service method is carried out offline by providing teaching and guidance at SMPI and SMK Diyaaul Musthafa. The results of the service show that teaching activities are carried out by providing Civics material to Diyaaul Mustafa Vocational High School students while the guidance process is by providing ICT guidance to Diyaaul Mustafa Middle School students. The conclusion of the service activities is that the service runs according to schedule while the impact is the fulfillment of the educational process at the Islamic Junior High School and Diyaaul Mustafa Vocational High School.